Traumatic brain injury causes frontotemporal dementia and TDP-43 proteolysis. (6th August 2015) - Wang, H.-K.; Lee, Y.-C.; Huang, C.-Y.; Liliang, P.-C.; Lu, K.; Chen, H.-J.; Li, Y.-C.; Tsai, K.-J.
Highlights: TBI is associated with a greater occurrence of FTD. TBI increased TDP-43 proteolysis in rats. TBI induced impaired behaviors that were associated with TDP-43 and its fragments. Abstract: Traumatic brain injury (TBI) is a major risk factor for dementia. Recently, TBI has also been suggested as a risk factor for frontotemporal dementia (FTD), and plasma immunoreactivity to the TAR-DNA binding protein 43 (TDP-43) has been observed in both patients with acute TBI and long-term survivors of this condition. We used a population-based study to estimate and compare the risk of FTD in individuals with and without TBI. Furthermore, we used a rat model of TBI to show that increased TDP-43 proteolysis following TBI produces FTD-like impairments, including abnormal limb-clasping, and impaired performances in the Morris water maze. We recruited 24, 585 patients who received ambulatory or hospital care for TBI and 122, 925 patients without TBI for this study. Each individual was investigated for 4 years to evaluate FTD development, and data were analyzed by Cox proportional hazard regression. In the TBI rat model, behavior and TDP-43 inclusions were assessed following intracranial administration of a caspase-3 inhibitor or vehicle. FTD was more likely to occur in the TBI group than in the group without TBI (adjusted hazard ratio, 4.43; 95% confidence interval, 3.85–5.10; P  < 0.001). Rats developed behavioral impairments similar to those in patients with FTD after TBI. Further, the behavioral impairments were likely associated with TDP-43 short fragment mislocalization and accumulation. Our findings suggest that in humans, TBI is associated with a greater occurrence of FTD. Moreover, clinical FTD manifestations may be associated with TDP-43 proteolysis, since impaired behaviors in TBI rats were reminiscent of those in humans with FTD.